INFLUENCE OF WORKLOAD AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN DRAMAGA, BOGOR - Herlina, Andiani; Agung, Syahrum; Kusumah, Anuraga (Manager : Jurnal Ilmu Manajemen, 2023)
This research was conducted to find out how far between workload and work discipline on employee performance. The sample used in this study was 53 employee respondents in Dramaga District, Bogor Regency. The method used is to spread the questionnaire form to the respondents and the data is processed using a computer application. This research was conducted in Dramaga District, Bogor Regency. Workload and Work Discipline Variables on Employee Performance The results of validity test, reliability test, descriptive analysis, inferential statistics, determination, t test, f test. The results of this study show that partially the workload variable (X1) has a significant effect on variable ( Y) Employee performance in Dramaga District, Bogor Regency with t Count > t Table 3,439 > t table 2.008 and a significance value of 0.001 <0.05 and Partially the variable Work Discipline (X2) has a significant effect on Employee Performance (Y) in the District Dramaga Bogor Regency with a t count 3,295 > t table > t tabble 2.008 and a significance value of 0.002 <0.05 Simultaneously, the Workload Variable (X1) and Work Discipline Variable (X2) have a significant effect on Employee Performance Variables (Y ) In Dramaga District, Bogor Regency, with f count > f table = 10,253 > F table 2.79 and a significant value of 0.000 <0.05.